EMPATI DALAM RASISME DENGAN METODE DESIGN THINKING - Yefta Christian; Robin Robin; Sandy Tio; Ridho Kurnia; Nanda Silvia Sovitasari; Vigho raziansyah; Steven Steven; Rizki Alamsyah; Vani Andini; Joana Stefhanie Saliama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Racism has always been something we have fought against as a trigger for the division. We live in an area with a variety of ethnicities, races, cultures, and skin colors. In Batam City, there are still many minorities who are affected by racism, especially students. There are many problems that arise as a result of racism, which is more specifically discussed about skin color. So far, skin color has become very controversial because white people feel superior to black people so that social inequality and discrimination are very visible. The method used is the concept of design thinking by making videos and distributing them to students affected by racism. The results obtained from the respondents show that through design thinking, this video provides educational value to students to value and respect diversity. So that there is no difference between whites and blacks because we have the same language, namely Indonesian.